2017
DOI: 10.1016/j.yhbeh.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Social evaluative threat with verbal performance feedback alters neuroendocrine response to stress

Abstract: Laboratory stress tasks such as the Trier Social Stress Test (TSST) have provided a key piece to the puzzle for how psychosocial stress impacts the hypothalamic-pituitary-adrenal axis, other stress-responsive biomarkers, and ultimately wellbeing. These tasks are thought to work through biopsychosocial processes, specifically social evaluative threat and the uncontrollability heighten situational demands. The present study integrated an experimental modification to the design of the TSST to probe whether additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 104 publications
3
14
1
Order By: Relevance
“…Support for this theory was not apparent as we revealed positive HPA-HPG associations, and we revealed that the relationship between SS and testosterone reactivity remained significant even with cortisol in the model. Instead, our findings support a "coupling" model where the HPA and HPG axis positively modulate one another, and extends the subset of that literature that examines acute reactivity (Marceau et al, 2014;Phan et al, 2017;Zakreski et al, 2019) to skydiving. This suggests situations that are both stressful and exciting, like skydiving, may simultaneously activate both the HPA and HPG axes, possibly helping the individual to navigate a situation which is thrilling precisely because it is both stressful and challenging.…”
Section: Cortisol and Testosterone Response To Skydivingsupporting
confidence: 86%
See 1 more Smart Citation
“…Support for this theory was not apparent as we revealed positive HPA-HPG associations, and we revealed that the relationship between SS and testosterone reactivity remained significant even with cortisol in the model. Instead, our findings support a "coupling" model where the HPA and HPG axis positively modulate one another, and extends the subset of that literature that examines acute reactivity (Marceau et al, 2014;Phan et al, 2017;Zakreski et al, 2019) to skydiving. This suggests situations that are both stressful and exciting, like skydiving, may simultaneously activate both the HPA and HPG axes, possibly helping the individual to navigate a situation which is thrilling precisely because it is both stressful and challenging.…”
Section: Cortisol and Testosterone Response To Skydivingsupporting
confidence: 86%
“…The HLM modeled testosterone changes in response to skydiving at Level 1 in order to model time-varying predictors of each sample of testosterone. This approach is similar to our prior work (Phan et al, 2017), and our strategy for modeling cortisol reactivity to skydiving previously with this sample (Meyer et al, 2015). The preliminary model was built:…”
Section: Analysis Planmentioning
confidence: 93%
“…The sample as a whole did not show a further increase in cortisol levels at T1 compared to the baseline measurement, with mean cortisol levels at baseline and T1 being nonsignificantly different from one another, F (1, 54) = 0.78, p = .382 (see Table for all M s and SD s). This pattern is known to occur when a pretask cortisol sample is taken after the participants have been in the lab for some time, as the novelty of the lab situation initiates the stress response for some individuals, causing feedback inhibition that can suppress a later response to the applied stressor (e.g., Duan et al, ; Phan et al, ; Ruttle, Shirtcliff, Armstrong, Klein, & Essex, ). Further probing indicated that a potentially nontrivial minority ( n = 19, 30%) of participants demonstrated a cortisol increase from their pretask baseline compared to some point in the post‐task period ( n = 15 immediately from BL to T1; n = 3 peaking later at T2, T3; n = 1 peaking at T4).…”
Section: Resultsmentioning
confidence: 99%
“…This is ideal, given that neither linear nor quadratic growth models are well suited to cortisol data (see Ji, Negriff, Kim, & Susman, ; Lopez‐Duran et al, ). The FCSI model also does not assume that change trajectories are the same for all individuals (Wood, ), which is important in the case of cortisol because not all individuals experience their peak cortisol at the same measurement time point (e.g., Lopez‐Duran et al, ; Phan et al, ). Because the factor loadings for the latent intercept are all fixed to a value of one, the meaning of the FCSI model's latent intercept can be understood as the portion of variance in cortisol values attributable equally to vertical elevations across all time points in the model or, in other words, as the individual variability in overall amplitude at which each cortisol curve plays out (see Wood, ; Wood & Jackson, ).…”
Section: Methodsmentioning
confidence: 99%
“…1 Similar to cortisol, DHEA is released in response to social and physical stressors that stimulate a biological cascade culminating with adrenocorticotrophic hormone (ACTH) acting on cells in the adrenal cortex. 2 DHEA levels are both responsive to acute stress, [3][4][5] and are shown to be altered following exposure to chronic stress and early-life stress. [6][7][8] DHEA was selected as the target of the present study because it acts widely on physiologic processes in both the brain and periphery.…”
mentioning
confidence: 99%